Physical culture and sport in Soviet society : propaganda, acculturation, and transformation in the 1920s and 1930s - Grant, Susan (New York : Routledge, 2012)
"From its very inception the Soviet state valued the merits and benefits of physical culture, which included not only sport but also health, hygiene, education, labour and defence. Physical culture propaganda was directed at the Soviet population, and even more particularly at young people, women and peasants, with the aim of transforming them into ideal citizens. By using physical culture and sport to assess social, cultural and political developments within the Soviet Union, this book provides a new addition to the historiography of the 1920s and 1930s as well as to general sports history studies. "--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sports and state -- Soviet Union -- History; Sports administration -- Soviet Union -- History; Sports -- Social aspects -- Soviet Union -- History; Electronic books